2017
DOI: 10.1055/s-0043-119363
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Aneurysmal Subarachnoid Hemorrhage During Pregnancy as an Interdisciplinary Task

Abstract: Maternal aneurysmal subarachnoid hemorrhage (aSAH) during pregnancy presents a challenge regarding treatment and management. Due to the limited number of cases there are no treatment guidelines available. Thus, treatment is usually done on a case-by-case basis. Here we report on four cases of aSAH during pregnancy, describing the different management strategies and suggesting a possible treatment algorithm. Patients treated between 2003 and 2013 in our center were included in this retrospective study. Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Some studies, however, have found no increased incidence of SAH in pregnancy, and there is paucity of data regarding the potential risk conveyed by either twin pregnancy or IVF procedures. 5 To our knowledge, this is the first case reported of a SAH in a woman with history of IVF conception. She had the well-established risk factors for SAH of a right MCA aneurysm, hypertension and a high BMI.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Some studies, however, have found no increased incidence of SAH in pregnancy, and there is paucity of data regarding the potential risk conveyed by either twin pregnancy or IVF procedures. 5 To our knowledge, this is the first case reported of a SAH in a woman with history of IVF conception. She had the well-established risk factors for SAH of a right MCA aneurysm, hypertension and a high BMI.…”
Section: Discussionmentioning
confidence: 72%
“…Some groups have suggested a therapeutic algorithm to simplify the management of SAH in pregnancy which considers the gestation, radiation exposure and location of an aneurysm to advise treatment and timing of delivery. 5 Further work, however, is required to develop recommendations for the standardised management of CVA in pregnant women and in particular those undergoing IVF. 19…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations